Growth Response, Serum Biochemistry and Organ Histopathology of Broilers Fed Diets supplemented with Graded levels of Petiveria alliacea Root Meal - Odetola , Olubayo M.; Adejinmi, Olufunmilayo O.; Owosibo, Olatunde A.; Banjo, Omotoyosi T.; Awodola-Peters, Omolade O. (International Journal of Poultry Science, 2018)
Background and Objective: This study was conducted to assess the growth response, serum biochemistry and organ histopathology of broiler chickens. Materials and Methods: A total of 180 unsexed day old broiler chickens were used for this study. Broiler chickens fed diets supplemented with graded levels of Petiveria alliacea root meal (PRM) at 0, 500, 1000, 1500, 2000 and 2500 g/100 kg of feed in 8 weeks feeding trial. Data were collected on feed intake and weekly weight gain. Blood samples were collected from the animals through the wing web vein for serum biochemistry while samples of visceral organs and small intestine were collected from the animals after they were stunned and sacrificed. Results: Results revealed no significant difference (p>0.05) in all the growth response parameters examined. While Aspartate amino transferase were significantly (p